2005
DOI: 10.1177/147323000503300510
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields Inhibit Endothelin-1 Production Stimulated by Thrombin in Endothelial Cells

Abstract: Electromagnetic field (EMF) radiation has been found to induce arteriolar dilatation, but the mechanism of action remains largely unknown. This study investigated the effect of EMF radiation on the production of endothelin-1 (ET-1), a potent vasoconstrictor, by cultured endothelial cells. EMF radiation reduced ET-1 basal levels in human umbilical vein and microvascular endothelial cells, but failed to reduce ET-1 basal levels in bovine and human aortic endothelial cells. EMF radiation significantly inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…It is now well accepted that thrombin induces endothelin, and levels of both are elevated in SSc [13], as well as in other pathological conditions of vascular endothelium [4]. Endothelin has been also reported to be an important endogenous factor promoting induction of myofibroblasts [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well accepted that thrombin induces endothelin, and levels of both are elevated in SSc [13], as well as in other pathological conditions of vascular endothelium [4]. Endothelin has been also reported to be an important endogenous factor promoting induction of myofibroblasts [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that thrombin differentiates normal lung fibroblasts to a myofibroblast phenotype via the PAR-1 receptor and via a PKC-dependent pathway [6]. Thrombin is known to induce ET-1 in various cell types [12,13]. Moreover, ET-1 and thrombin have similar pro-fibrogenic effects in lung fibroblasts and endothelial cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Direct evidence of the effect of a pulsed electromagnetic field signal configured for the Ca/calmodulin pathway on real-time nitric oxide production in a neuronal cell line, which could be eliminated by calmodulin and nitric oxide synthase inhibitors, has also recently been reported. Other effects of pulsed electromagnetic fields involving nitric oxide include the following: increased vasodilatation (Miura et al 1993), inhibition of the vasoconstrictor endothelin-1 (Morimoto et al 2005), increased neuronal regeneration (Kim et al 2002). Furthermore, it has been reported that the calmodulin/endothelial nitric oxide synthase/nitric oxide signaling pathway down-regulates both IL-1B and inducible nitric oxide synthase.…”
Section: Calcium Calmodulin Model For Nonthermal Interactionsmentioning
confidence: 99%
“…RF kaynaklı EMA nöronların elektrik aktivitesini, genomik yanıtlarını, nörotransmitter dengelerini, kan-beyin bariyerinin geçirgenliğini etkiler 57 . EMA radyasyon etkili bir vazokonstriktör olan endotelin-1 (ET-1) üretimi-ni düzenler ve nitrik oksit (NO) yolunda inhibitor etkileriyle aracılık eder 58 . Yaklaşık 1 mW/cm2 lik güç yoğunluğunda bir düz dalgaya karşılık gelen 2,5 W/kg SAR, amplitüd-modülasyonlu mikrodalgalar invitro hücre kültürlerinde biyolojik aktiviteleri olarak uygulanan düşük frekanslı, düşük enerjili, darbeli elektromanyetik alanlar (DFDEMA) kemik onarımını hızlandırır, kemik oluşumunu uyarabilir ve kaynama gecikmesi ya da kaynamayan kırıkların iyileştirilmesi için tedavide kullanılabilir.…”
Section: Yüksek Frekans Ema'ların Biyolojik Dokulara Ve Kırık Iyileșmunclassified